2018
DOI: 10.1093/mnras/sty2170
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal analysis of the interstellar medium: first application to Hi-GAL observations

Abstract: The multifractal geometry remains an under-exploited approach to describe and quantify the large-scale structure of interstellar clouds. In this paper, the typical tools of multifractal analysis are applied to Herschel far-infrared (70-500 µm) dust continuum maps, which represent an ideal case of study. This dust component is a relatively optically thin tracer at these wavelengths and the size in pixel of the maps is well suitable for this statistical analysis. We investigate the so-called multifractal spectru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 68 publications
2
35
0
Order By: Relevance
“…However, the extraction of a monofractal component covering all spatial scales and filling the whole field is a first step towards a better comprehension of how turbulence is related to the ISM gas structures. An important comparaison of multifractal analysis based on a box-counting approach has been recently done by Elia et al (2018) using Hi-GAL observations (a key programme of Herschel), fBm images, and numerical simulations. They found that all the investigated fields, which are located in the Galactic plane, exhibit a multifractal structure rather than a simple monofractal structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the extraction of a monofractal component covering all spatial scales and filling the whole field is a first step towards a better comprehension of how turbulence is related to the ISM gas structures. An important comparaison of multifractal analysis based on a box-counting approach has been recently done by Elia et al (2018) using Hi-GAL observations (a key programme of Herschel), fBm images, and numerical simulations. They found that all the investigated fields, which are located in the Galactic plane, exhibit a multifractal structure rather than a simple monofractal structure.…”
Section: Discussionmentioning
confidence: 99%
“…Fractal models fail to reproduce the common sharp transition in intensity seen in the ISM. Recently, Elia et al (2018) has shown that fBm models are not a good approximation of the ISM, but that multifractal analysis offers a more complete characterisation of molecular cloud structures.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Elia et al (2018) recently emphasised that the monofractal approach to characterising ISM structures underlies a certain degree of degeneracy as the statistical description of the regions is based on a single parameter, the fractal dimension. They proposed to analyse the multifractal properties of ISM structures in Galactic dust-continuum maps using the boxcounting approach.…”
Section: Introductionmentioning
confidence: 99%
“…Since in the interstellar medium there exist structures spanning a large dynamic range of spatial scales, and since there is evidence for self-similarity across parts of this dynamic range, there have been several attempts to characterise the interstellar medium, and in particular star forming clouds, with fractal or multi-fractal parameters (e.g. Beech 1987;Bazell & Desert 1988;Falgarone et al 1991;Hetem & Lepine 1993;Stutzki et al 1998;Bensch et al 2001;Chappell & Scalo 2001;Sánchez et al 2005;Ossenkopf et al 2008a;Kauffmann et al 2010;Schneider et al 2013;Elia et al 2014; E-mail: matthew.bates@astro.cf.ac.uk Rathborne et al 2015;Elia et al 2018). Such characterisations can, in principle, allow one (a) to constrain the three dimensional structures and dynamics that underlie the observed two-dimensional projections; (b) to evaluate whether two observed regions might be statistically similar, even if their detailed structures are quite different; and (c) to compare the results of numerical simulations with observations, and with one another.…”
Section: Introductionmentioning
confidence: 99%
“…Beech 1987; Bazell & Desert 1988;Falgarone et al 1991;Hetem & Lepine 1993;Sánchez et al 2005;Federrath et al 2009;Rathborne et al 2015), and the box-counting dimension, D BC (e.g. Sánchez et al 2005;Federrath et al 2009;Elia et al 2018); D PA is usually preferred to D BC , because it tends to give less noisy results. A second group of metrics derive from structure, or structure-like, functions (e.g.…”
Section: Introductionmentioning
confidence: 99%